EVALUASI TATA KELOLA SISTEM INFORMASI PENGELOLAAN DANA SEKOLAH - Anggi Aditya Fahmi; Aprina Nugrahesthy Sulistya Hapsari (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
The Industrial Revolution 4.0, which is characterized by disruptive technology, demands the optimal use of information systems and information technology. In addition to being able to support the organization's business processes, information technology is certainly also free from all threats such as fraud, which means that there is a need for information technology audits. School X is an entity that requires an assessment of information technology audits because it manages school funds. So it is necessary to evaluate IT governance to find out the achievement of organizational maturity using the COBIT 5 framework which then provides recommendations to be taken into consideration in future IT management using the COBIT framework 5. This research focuses on the EDM process domain (evaluate, direct, and monitoring) and APO (align, plan, organise) with a qualitative descriptive approach. The results of this study indicate that the organization has reached maturity levels at level 1 (Performed Process), level 2 (Managed Process) and level 3 (Established Process) which means that the organization has implemented all EDM and APO domain processes at COBIT 5 except APO05 subdomains (managed portfolio) because the organization is nonprofit oriented, it is at level 0 (incomplete process). But it has not fully documented and communicated the process for organizational efficiency.